Efficacy and safety of ozanimod in multiple sclerosis: Dose-blinded extension of a randomized phase II study. (August 2019) - Cohen, Jeffrey A; Comi, Giancarlo; Arnold, Douglas L; Bar-Or, Amit; Selmaj, Krzysztof W; Steinman, Lawrence; Havrdová, Eva K; Cree, Bruce AC; Montalbán, Xavier; Hartung, Hans-Peter; Huang, Vivian; Frohna, Paul; et al.
Background: Ozanimod, an oral immunomodulator, selectively targets sphingosine 1-phosphate receptors 1 and 5. Objective: Evaluate efficacy, safety, and tolerability of ozanimod in relapsing multiple sclerosis. Methods: In the RADIANCE Part A phase II study (NCT01628393), participants with relapsing multiple sclerosis were randomized (1:1:1) to once-daily ozanimod hydrochloride (0.5 or 1 mg) or placebo. After 24 weeks, participants could enter a 2-year, dose-blinded extension. Ozanimod-treated participants continued their assigned dose; placebo participants were re-randomized (1:1) to ozanimod hydrochloride 0.5 or 1 mg (equivalent to ozanimod 0.46 and 0.92 mg). Results: A total of 223 (89.6%) of the 249 participants completed the blinded extension. At 2 years of the extension, the percentage of participants who were gadolinium-enhancing lesion-free ranged from 86.5% to 94.6%. Unadjusted annualized relapse rate during the blinded extension (week 24—end of treatment) was 0.32 for ozanimod hydrochloride 0.5 mg → ozanimod hydrochloride 0.5 mg, 0.18 for ozanimod hydrochloride 1 mg → ozanimod hydrochloride 1 mg, 0.30 for placebo → ozanimod hydrochloride 0.5 mg, and 0.18 for placebo → ozanimod hydrochloride 1 mg. No second-degree or higher atrioventricular block or serious opportunistic infection was reported. Conclusion: Ozanimod demonstrated sustained efficacy in participants continuing treatment up to 2 years and reached similar efficacy in participants who switched from placebo; no unexpected safety signals emerged.